Rancang Bangun Aplikasi Penentuan Bahan Makanan Berdasarkan Status Gizi Pada Pasien Rawat jalan - Sukasdi, Lailatul Fitri Kanthi; Tjandrarini, Asteria; Amelia, Tan (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
: During this time, foood stuff determination with applying balanced nutrient for hospitalization patient have been controled. For outpatient food stuff determination which applied balanced nutrition, need to be consulted with nutritionist. The outpatient can’t determine their food stuff independently where it can be supporting their healing phase.Based on the issues that has been described, then it is needed an application that can make consultating easier for the patient. Thats why it is created a food stuff determination application based on nutrient status for outpatient.This application can determine nutrient status , calori need and food stuff based on desease story of the patient. This application using antropometri to determine nutrient status and using harris benedict formula for calori need. Then to determine a food stuff that suitable with calori’s need of the patient are matched by nutrient consumption. Those application will be run based on web then this application can be used widely, because it is in order to be acces whenever and wherever by public.Based on the test result, it can be concluded that this application has been fullfilled the expectation. This application has been able to determine nutrition status, calori need and food stuff which is suitable with calori need for outpatient with specific desease story.